2011
DOI: 10.1108/00070701111131700
|View full text |Cite
|
Sign up to set email alerts
|

Critical factors for effective implementation of the HACCP system: a Pareto analysis

Abstract: PurposeThe main objective of this paper is to examine the existing literature on food safety assurance systems and record the vital critical factors that affect the implementation of these systems, in the context of the global food‐processing sector, for the benefit of researchers and industries.Design/methodology/approachA range of published (1995‐2008) articles on food safety is explored that lists the motives for and the barriers to the implementation of the Hazard Analysis of Critical Control Point plan in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 40 publications
4
79
0
3
Order By: Relevance
“…These measures aim to prevent food contamination, such contamination are chemical, physical or microbiological. The programs commonly used in this area are Good Manufacturing Practices (GMP), Hazard Analysis and Critical Control Points (HACCP), British Retail Consortium (BRC) and Global Food Safety Initiative (GFSI), frequently found in the food industry, are obligatory by law, and others are implemented voluntarily by the food chain members [3].…”
Section: Food Security Programsmentioning
confidence: 99%
“…These measures aim to prevent food contamination, such contamination are chemical, physical or microbiological. The programs commonly used in this area are Good Manufacturing Practices (GMP), Hazard Analysis and Critical Control Points (HACCP), British Retail Consortium (BRC) and Global Food Safety Initiative (GFSI), frequently found in the food industry, are obligatory by law, and others are implemented voluntarily by the food chain members [3].…”
Section: Food Security Programsmentioning
confidence: 99%
“…The concept comes from Pareto's principle that there are few factors blamed for most of problems (Fotopoulos et al, 2011). In addition, the parameters that have critical level of technical criticality should also be included in the control even though they do not account for 80% of total failure costs.…”
Section: Methods 1: Focus First On Cost Criticalitymentioning
confidence: 99%
“…To establish equivalence between two similar HACCP plans, it is necessary to be capable to measure their efficacy by incorporating quantitative risk-based decisions during the process of implementation and relating HACCP plans to public health goals, such as reducing food-borne diseases (Orris, 1999). Fotopoulos et al (2011) have reported the results of a study, which explored motives and constraints to implementation of the HACCP system in the literature (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) on food safety. The authors concluded that 11 elements represent most of the motives and constraints identified, these being the 'vital few' factors instrumental for implementation of HACCP system.…”
Section: Review Of Factors Which Have Been Described To Affect Haccp mentioning
confidence: 99%
“…According to the results, the major difficulties involved were staff training and motivation, as well as product flexibility reduction. Other researchers have also reported that staff limitations might be a barrier to proper HACCP implementation (Henson et al 1999, Eves and Dervisi 2005, Fotopoulos et al 2011. Finally, Semos and Kontogeorgos (2007) investigated also managerial opinions regarding potential benefits of HACCP implementation.…”
Section: Review Of Factors Which Have Been Described To Affect Haccp mentioning
confidence: 99%